2020
DOI: 10.3346/jkms.2020.35.e289
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Adenosine Monophosphate-activated Protein Kinase by Telmisartan Decreases Basal and Platelet-derived Growth Factor-stimulated Vascular Smooth Muscle Cell Proliferation via Inhibiting the Mammalian Target of Rapamycin/p70 S6 Kinase Signaling Axis

Abstract: Background: Telmisartan, an angiotensin II type 1 receptor blocker (ARB), is widely used to treat hypertension by blocking the renin-angiotensin-aldosterone system. Although abnormal proliferation of vascular smooth muscle cells (VSMCs) is a well-established contributor to the development of various vascular diseases, such as atherosclerosis, the effect of telmisartan on VSMC proliferation and its mechanism of action have not been fully revealed. Herein, we investigated the molecular mechanism whereby telmisar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The other plausible explanation, not inconsistent with the first, is that HuMoSCs (or their supernatant) could inhibit the mTOR complex by acting on another PDGF-activated pathway, such as AMP-activated protein kinase (AMPK). Indeed, telmisartan has been shown to inhibit rat VSMC proliferation via AMPK-dependent inhibition of mTOR phosphorylation ( 34 ). Along this line, another study demonstrated that jujuboside B antagonizes PDGF-BB-induced phenotypic switch, proliferation and migration of VSMCs partly through AMPK/PPAR-γ pathway ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The other plausible explanation, not inconsistent with the first, is that HuMoSCs (or their supernatant) could inhibit the mTOR complex by acting on another PDGF-activated pathway, such as AMP-activated protein kinase (AMPK). Indeed, telmisartan has been shown to inhibit rat VSMC proliferation via AMPK-dependent inhibition of mTOR phosphorylation ( 34 ). Along this line, another study demonstrated that jujuboside B antagonizes PDGF-BB-induced phenotypic switch, proliferation and migration of VSMCs partly through AMPK/PPAR-γ pathway ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rat aortic VSMCs were isolated and cultured as previously described. 25 Briefly, six-week-old male Sprague-Dawley (SD) rats were euthanized with CO 2 gas and subsequent cervical dislocation, and their thoracic aortas were immediately dissected. Connective tissues were removed, and the endothelium was denuded by gentle rubbing.…”
Section: Methodsmentioning
confidence: 99%
“… 19 20 Of the many downstream targets of AMPK, the mammalian target of rapamycin (mTOR)/p70 S6 kinase (p70S6K) signaling pathway responsible for the regulation of protein synthesis, cell proliferation, and metabolism 19 21 is blocked when AMPK is activated, leading to the inhibition of cell proliferation in various types of cells. 22 23 24 25 A recent study reported that activation of AMPK by telmisartan, an angiotensin II type 1 receptor blocker, decreases basal and PDGF-stimulated VSMC proliferation via inhibiting the mTOR/p70S6K signaling pathway. 25 Nevertheless, no study has been reported on whether FIR irradiation inhibits VSMC proliferation and the AMPK/mTOR/p70S6K signaling axis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Lu et al found that nesfatin-1, a multifunctional adipocytokine, promotes VSMC proliferation by activating the PI3K/Akt/mTOR signaling pathway and plays a key regulatory role in hypertension and vascular remodeling. 109 In addition, a study showed that tanshinone I, a cardiovascular therapeutic agent, inhibits VSMC proliferation by inhibiting the PI3K/mTOR signaling pathway, facilitating the treatment of vascular diseases such as hypertension. 110 These results suggest that mTOR is implicated in the development and progression of hypertension, and mTOR-mediated VSMC proliferation plays a role in hypertension.…”
Section: Crucial Role Of Mtor Signaling In Vascular Proliferative Dis...mentioning
confidence: 99%